425 Extra-Anatomical Detour Ureteric Stents: Our District General Hospital Experience of 50 Patients with a Minimum Follow Up of 6 Months. (19th August 2022) - Rahman, A; Quraishi, MK; Mackie, S; Watson, G
Abstract: Aim: Extra-Anatomical Detour Stents offer a viable modality of decompression particularly in the context of malignancies; with the absent need for changes of stents, cosmetically better than nephrostomies and fewer admissions associated with blockages/infections. Our aim was to assess the safety and feasibility of performing detour stents in a district general hospital. Method: A review of prospectively collected data on all patients undergoing detour stents between 2016 and 2021 was undertaken. This enabled a possible follow up period of 6 months, provided the patients remained alive. A statistical package was utilised for the analysis of the collected data. Results: Fifty patients were identified to have undergone detour stent insertion with malignancy being the indication in 90% of cases. Seven patients required a further eleven procedures with the most common being due to repositioning of the stent (36%) or change of stent due to infection (27%). Four patients passed away within 60 days of their procedure. Four patients had their stents eventually replaced with nephrostomies and a patient no longer required the detour stent due to resolution of their obstructive pathology. Nine patients are currently being followed up and thirty-six patients from the original cohort passed away with functional detour stents. Their median survival time post-procedure was 164 days. Conclusions: Extra-Anatomical Detour Stents offers patients with obstructing renal tract secondary to malignancy a better quality of life when compared with nephrostomy. Continued caseload and refinement of surgical technique would lead to further optimised surgical outcomes.